Acceleration Planning of the Closed Five-bow-shaped-bar Linkage based on Energy Consumption Analysis - Yu Lianqing; Zeng Xiangkuo; Li Hongjun; Wu Zijun; Meng Yunhong (Jixie chuandong, 2020)
In order to reduce the energy consumption of a robot of the closed five-bow-shaped-bar linkage rolling along a straight line，the effect of the maximum rolling acceleration under the constant potential energy rolling strategy and the variable potential energy rolling strategy on the total energy consumption of the system is studied.A modified trapezoidal curve with adjustable maximum rolling acceleration is adopted as the rolling angle acceleration law of the system，and the joint trajectories is obtained by using the rolling strategies of constant potential energy and variable potential energy respectively.On this basis，considering the viscous friction in the joints，the Lagrange equation with dissipation function is used to solve inverse dynamics solution，and the total energy consumption of the system is calculated by the energy consumption equation.The calculation shows that the total energy consumption of the system decreases first and then increases with the increase of the maximum rolling acceleration，and using the constant potential energy rolling strategy is beneficial to reducing the total energy consumption of the system.Finally，the correctness of theoretical analysis is verified by Adams simulation.